2014
DOI: 10.1016/j.cell.2014.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Communication in the Dynein Motor Domain

Abstract: SUMMARY Dyneins power microtubule motility using ring-shaped, AAA-containing motor domains. Here, we report X-ray and electron microscopy (EM) structures of yeast dynein bound to different ATP analogs, which collectively provide insight into the roles of dynein’s two major ATPase sites, AAA1 and AAA3, in the conformational change mechanism. ATP binding to AAA1 triggers a cascade of conformational changes that propagate to all six AAA domains and cause a large movement of the “linker,” dynein’s mechanical eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
271
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(288 citation statements)
references
References 65 publications
(92 reference statements)
16
271
1
Order By: Relevance
“…We therefore assume that these two sites are unoccupied and that nucleotide occupancy of the Pex1 subunits has a major effect on subunit spacing. A correlation between subunit spacing and nucleotide occupancy has also been observed in recent structures of dynein (50). In our ATPγS structure, some of the occupied sites might contain ADP, as the differences from the ADP structure are only small and ATPγS can slowly be hydrolyzed or be contaminated with ADP.…”
Section: Discussionmentioning
confidence: 79%
“…We therefore assume that these two sites are unoccupied and that nucleotide occupancy of the Pex1 subunits has a major effect on subunit spacing. A correlation between subunit spacing and nucleotide occupancy has also been observed in recent structures of dynein (50). In our ATPγS structure, some of the occupied sites might contain ADP, as the differences from the ADP structure are only small and ATPγS can slowly be hydrolyzed or be contaminated with ADP.…”
Section: Discussionmentioning
confidence: 79%
“…However, recent reports relate linker conformation to dynein's ATPase activities. In the absence of load, ATP at AAA3 blocks reorientation of the linker from the post-to the prepowerstroke conformation (9). In addition, binding of the cofactor Lis1, which mechanically obstructs linker movements, uncouples AAA1's ATPase activities from changes in MT-binding affinity (44).…”
Section: Discussionmentioning
confidence: 99%
“…Although AAA3 plays an important role in controlling dynein-MT attachment (22,23,25), the details are just emerging. By probing dynein-MT interactions in the absence of load (9,34) and with force applied to the dynein C terminus (34), DeWitt et al and Bhabha et al concluded that AAA3 must be in a posthydrolysis state for ATP-induced, AAA1-mediated MT release. Our MTBR and C-terminal pulling results support these findings, but if tension is applied via the linker, then AAA1-mediated MT release is allowed when AAA3 enters the ATP state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations